Corporate Guarantee Legal Certainty Provided Without Shareholder Approval - Dianrachma, Mitari; Sugiyono, Heru; Sakti, Muthia (Lafadz Jaya Publisher, 2024)
The agreement providing a corporate guarantee does not provide a limit on the nominal amount that will be guaranteed by the corporate guaranteed provider because the corporate guarantee provider will guarantee the entire debt including interest, fines, fees and other amounts of money that must be paid. In Indonesian limited liability company law, directors are required to seek shareholder approval in the case of pledging more than fifty percent of the company's assets, but in practice, approval from shareholders is not always required to provide a corporate guarantee. Especially in the case of corporate guarantees known as limited corporate guarantees, where the guarantee value does not exceed fifty percent of the Company's total assets. The aim of this research is to analyze the legal certainty of providing corporate guarantees without shareholder approval for credit applications whose value is less than fifty percent of the Company's assets. This type of research is normative juridical, namely a type of research with a conceptual approach. This research has the result that a corporate guaranteed agreement to guarantee the value of a credit facility whose value is not more than 50% of the company's assets provided without shareholder approval does not provide legal certainty.